Complete chloroplast genome sequence of a bulbous flowering plant, Allium triquetrum Linnaeus, 1753 (Amaryllidaceae). Issue 11 (2nd November 2022) - Min, Xiaoxiao; Li, Peiling; Gong, Shoufu; Zhu, Qingsong
Abstract: Allium triquetrum (Linnaeus, 1753) is a bulbous flowering plant of the genus Allium (Amaryllidaceae), native to the Mediterranean basin, and is now widespread and invasive in different parts of the world via ornamental horticultural trade. However, to date, the genomic study of A. triquetrum has lagged, which impedes the development of appropriate utilization and management practices for this species. Here, we report the complete chloroplast genome sequence of A. triquetrum . The chloroplast genome size of A. triquetrum was 153, 298 bp, consisting of a pair of inverted repeat regions (26, 547 bp), separated by a large single-copy (82, 875 bp) region and a small single-copy (17, 329 bp) region. Genome annotation predicted 133 genes, including 87 protein-coding genes, 38 tRNA genes, and eight rRNA genes. Phylogenetic analysis based on 60 whole chloroplast genome sequences of Allium species suggested that A. triquetrum and A. moly are sister to each other along with the clade of A. fasciculatum, A. hookeri, and A. macranthum .